Русский и тюркские языки: билингвизм и полилингвизм - Джусупов, Mаханбет (Studia Rossica Posnaniensia, 2014)
The paper focuses on the issue of contact between Russian and the Turkic Languages in Central Asia with regard to bilingualism and multilingualism. In the Central Asian Republics Russian is the second or third most frequently used language. For the last twenty years the number of bilingual and multilingual speakers who use Russian has been decreasing. This fact is primarily related to the new sociolinguistic situation in the Central Asian Republics.